A Comparison of 3D Facial Features in a Population from Zimbabwe and United States - Bhaskar, Elvin; Kau, Chung H. (European Journal of Dentistry, 2020)
Objectives The purpose of this study was to determine the differences in three-dimensional (3D) facial features in a population from Zimbabwe and the United States. In addition, this study seeks to establish an average facial template of each population allowing clinicians to treat patients according to their cultural esthetic perceptions.Materials and Methods Three hundred one subjects from Zimbabwe and the United States were carefully selected and recruited for the study. Each subject presented with a normal facial profile, no asymmetries, and normal body mass index. The 3D images were captured using the 3dMD cameras. All images were further separated into male and female groups of the respective populations and imported to a dedicated software for analysis.Statistical Analysis The 3D facial images were constructed using Rapidform 6 software to recreate a composite facial average for each group representing a male and female average 3D face of Zimbabwean (Zim) and United States origin.Results The linear measurements showed that the maximum average distance between the Zim-M and Zim-F was 1.24 mm and the minimum distance between the African American (AA)-M and AA-F was 0.24 mm. This was the absolute distance. When the signed linear measurements were taken into consideration, the maximum average distance between Zim-F and AA-M was 1.22 mm and the least average distance between the Zim-M and AA-M was 0.22 mm. The absolute color histograms showed greatest similarity between the Zim-M and AA-M at 58% and the Zim-F had a 25 and 27% similarity with the AA-F and Zim-M, respectively.Conclusion The Zim-F showed the most variable features with a broader face, prominent forehead, and retruded alar base compared with their male counterparts and the Zim-M showed a wider prominent malar/zygomatic region, and prominent lateral supraorbital regions. There was a high similarity of 58% between the Zim-M and the AA-M, with the Zim-M showing a more protrusive superciliary arches, and a lateral zygomatic region tapering to the root of the nose.
Keywords: surface acquisition systems; 3D faces; 3D imaging; 3D analysis